Objeto Malasartes e a mudança de foco no perfil de professor de Artes Visuais - Vinhas, Neusa Loreni (2013)
This paper presents the trajectory of building a learning object in visual arts, called “Malasartes.” Provocations are focused on the object creation and involvement of the author / creator in choosing art images for use in classes, articulated the concepts and reflections in this way. The organization of the text presents a thread outlined the author’s professional history